An Unprecedented Retro‐Mumm Rearrangement Revealed by ESI‐MS/MS, IRMPD Spectroscopy, and DFT Calculations1. Issue 27 (26th April 2018) - Iacobucci, Claudio; Reale, Samantha; Aschi, Massimiliano; Oomens, Jos; Berden, Giel; De Angelis, Francesco
Abstract: Brønsted acids and protic solvents mediate acyl transfer, known as the Mumm rearrangement, from imidates to the corresponding acylamides. This represents a key step in several reactions, for example, the Ugi four‐component reaction (U‐4CR) and Passerini three‐component reaction (P‐3CR). Herein, an unprecedented break of the non‐reversibility of the Mumm rearrangement is reported. A combination of electrospray tandem mass spectrometry (ESI‐MS/MS), infrared multiphoton dissociation (IRMPD) ion spectroscopy and theoretical calculations demonstrates the occurrence of the retro‐Mumm rearrangement of protonated isopeptides in the gas phase. In the gas phase, the extra proton acquired during ESI promotes the backward isomerisation reaction in a catalytic fashion. Abstract : Going backwards : The Mumm rearrangement is the key intramolecular acyl transfer occurring in the Ugi four‐component (U‐4CR) and Passerini three‐component (P‐3CR) reactions. A combination of electrospray tandem mass spectrometry, infrared multiphoton dissociation (IRMPD) ion spectroscopy and theoretical calculations demonstrates the occurrence of the retro‐Mumm rearrangement of protonated isopeptides in the gas phase (see figure).